SOME EXISTING PROBLEMS IN CALCULATING THE GROSS DOMESTIC PRODUCT AND ITS COMPONENTS USING THE FINAL CONSUMPTION METHOD AND RECOMMENDATIONS FOR ITS IMPROVEMENT - Berdakh Joldasbayevich Mirzanov; Orinbaeva Maxinur Quatbaevna; Eshbanbetov Elmurat Maxsetbay uli (Galaxy International Interdisciplinary Research Journal, 2023)
This article explores the challenges faced in calculating the Gross Domestic Product (GDP) and its components using the final consumption method. It highlights the importance of adhering to international standards and standardized methods to ensure accurate and comparable measurements across countries. The article discusses the limitations of current measurement practices, including data availability and the inclusion of the informal and shadow economy. It emphasizes the need for improved calculation methods and data collection techniques to provide more reliable GDP estimates. The findings of this study have implications for policy decisions and understanding global economic trends. The article concludes by providing recommendations for enhancing the accuracy and reliability of GDP calculations, which can contribute to better economic analysis and decision-making.